Finite element simulations on erosion and crack propagation in thermal barrier coatings - Ma, Z.; Fu, L.; Yang, L.; Zhou, Y.; Lu, Chunsheng (Walter de Gruyter, Berlin/Boston, 2014)
Erosion of thermal barrier coatings occurs when atmospheric or carbon particles from the combustion chamber are ingested into aviation turbine engines. To understand the influence of erosion on the service life of thermal barrier coatings, we introduce the erosion and crack propagation models, and then by using finite element simulations, determine the relationship between the penetrating depth, the maximum principle stress and impingement variables such as velocity and angle. It is shown that cracks nucleate and extend during the erosion process and the length of a crack increases with the increase of the particle velocity and impact angle.